1978
DOI: 10.1128/jb.136.1.369-380.1978
|View full text |Cite
|
Sign up to set email alerts
|

Cloned DNA fragment specifying major outer membrane protein a in Escherichia coli K-12

Abstract: Plasmid pMC44 is a recombinant plasmid that contains a 2-megadalton EcoRI fragment of Escherichia coli K-12 DNA joined to the cloning vehicle, pSC101. The polypeptides specified by plasmid pMC44 were identified and compared with those specified by pSC101 to determine those that are unique to pMC44. Three polypeptides specified by plasmid pMC44 were localized in the cell envelope fraction of minicells: a Sarkosyl-insoluble outer membrane polypeptide (designated M2), specified by the cloned 2-megadalton DNA frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It has been suggested that protein a is revolved in repression of capsular polysaccharide synthesis [20,21 ]. The strains lacking a which were described here, however, were normal with respect to mucoidy; that is, when grown on minimal plates at 30°C or 37°C, they formed mucoid colonies only at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that protein a is revolved in repression of capsular polysaccharide synthesis [20,21 ]. The strains lacking a which were described here, however, were normal with respect to mucoidy; that is, when grown on minimal plates at 30°C or 37°C, they formed mucoid colonies only at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…Protein labeling and analysis by PAGE-SDS. Plasmidcontaining minicells were isolated and labeled with [35S]methionine as described previously (13,47). Whole cells with or without plasmids were induced with nalidixic acid and labeled with [35S]methionine as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Protein samples and standards were prepared and subjected to PAGE-SDS in one dimension as described previously with approximately equal quantities of total radioactivity in each gel slot (13,47). The preparation of cells for twodimensional gel electrophoresis has been described previously (46), as have the details for the two-dimensional gel electrophoresis used here (3,(41)(42)(43).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A gene bank of C. trachomatis (serovar LI) DNA was prepared in the phage vector X1059. Choice of this vector was influenced by (i) the ease with which phage plaques, in contrast to bacterial colonies, can be screened by an in situ radioimmunoassay (26), (ii) the reported toxicity of outer membrane proteins for E. coli when present on plasmid vectors (10), and (iii) the previously reported expression of a chlamydial antigen in this system (27). From this library 20 clones exhibiting various degrees of seroreactivity with serum (IHS) from a patient with a C. trachomatis L1 infection were selected.…”
Section: Discussionmentioning
confidence: 99%